Ciclo político e efeito aliança nas transferências para os municípios - Parente, José Inácio Silva (2019)
This work aims to analyze the influences of political cycles on voluntary transfers of resources from the State to the municipalities of Ceará between 2011 and 2018. The objective is to analyze the effects that electoral cycles have on voluntary transfers of resources between the state of Ceará through the Secretariat of Cities to the 184 municipalities of Ceará. From this perspective, the present study will compile information on voluntary transfers, in order to verify the existence or not of transfers to the municipalities, and how the political cycle and the mayor's party affiliation may influence the implementation of these transactions. For this purpose, a probit model will be estimated taking into account a cluster analysis for the municipalities. The data used were taken from the Ceará State Transparency Portal in the Contracts and Agreements Monitoring System (SACC), the IBGE and the Ceará Institute for Economic Research and Strategy (IPECE). The main results showed that there is an electoral cycle effect where the probability of voluntary transfers is higher in election years, and only a little higher for the municipalities that were linked to the governor's party.